Chernobyl : nuclear power plant explosion - Hamilton, Sue L. (Edina, Minnesota Abdo & Daughters, 1991)
Follows the heroic actions of a Soviet firefighter as he describes the disastrous nuclear plant accident at Chernobyl.
8 - 10 years
66156
Keywords: Chernobyl Nuclear Accident -- Chernobyl, Ukraine; Nuclear power plants -- Accidents